An approach for cost management model in Agile Software Development Projects / Zulkefli Mansor - Mansor, Zulkefli (Institute of Graduate Studies, UiTM, 2014)
The successful outcome of software development projects is a crucial issue for the economy at large. Yet, a majority of the software development projects carried out today fails when it comes to finishing on time, within budget and with requirements intact. The often cited reasons contributing to failure include inappropriate methodology, complex development processes, ineffective project management, project managers’ incompetence, ineffective communication, uncoordinated stakeholders and the lack of automated tools. Due to these challenges and limitations, organizations are looking into agile software development which offers the advantage of having simple processes, involving active customers and project teams. Subsequently, past researchers attempted to define the determinant factors for agile success but there is still much ambiguity about these factors and how they can be determined. This study extends and builds on past research by focusing on one of the core factors, that is, cost management.